DEVELOPMENT OF VIBRATION ISOLATOR USING MAGNETORHEOLOGICAL ELASTOMER MATERIAL BASED - Priyandoko, Gigih; Suwandono, Purbo; Ubaidillah (Journal of Applied Engineering Science, 2021)
Many vibration isolators, for instance, passive vehicle mounting device, have fixed stiffness. This article presents the development of the adjustable stiffness engine mounting magnetorheological elastomers (MREs) based to reduce vibration. The development of MREs vibration isolator is to design of engine mounting first step, for next step is to simulate the electromagnetic circuit. The housing material selection and MREs thickness were considered to equip sufficient, uniform magnetic fields to change the stiffness. The innovative magnetic circuit design includes the type and size of the wire and the number of the coil turns to obtain the best magnetic fields to eliminate vibration. Finite Element Method Magnetics (FEMM) software was utilized to show the effectiveness of the electromagnetic circuit in generating magnetic fields through the MREs. Finally, various current input influence to the MREs vibration isolator is investigated. The higher current input is more useful to eliminate vibration using MREs isolator system.
Keywords: magnetorheological, elastomer, vibration, isolator